(untitled) (Archives of Mechanics - Test, 1996)
Expressions for Kelvin moduli of orthotropic linearly elastic bodies in terms of Young’s moduli and Poisson’s ratios are presented. The check of the orthotropy criterion is posed as a variational problem.